Ankle and midfoot ligaments: Ultrasound with anatomical correlation: A review. Issue 107 (October 2018) - Döring, Seema; Provyn, Steven; Marcelis, Stefaan; Shahabpour, Maryam; Boulet, Cedric; de Mey, Johan; De Smet, Aron; De Maeseneer, Michel
Highlights: Provide an overview of recent advances in understanding of anatomy of the ankle and midfoot ligaments. Provide detailed ultrasound technique and detailed description of ultrasound appearance of ligaments. Use this knowledge as a base for structured reporting of the ankle and midfoot (ligaments). Abstract: We present a detailed overview of anatomical and US features of ankle and midfoot ligaments based on our own dissections and cadaver studies as well as US imaging in cadavers and volunteers. The ligament anatomy about the ankle and midfoot is complex. Most ligaments are superficial and hence very well accessible for US. US technique to obtain optimal visualization however is difficult and requires a learning curve. We discuss US technique in detail for each individual ligament. We divided the ligaments in different groups: tibiofibular ligaments, Bassett's ligament, lateral collateral ligament complex (anterior talofibular ligament, calcaneofibular ligament, lateral talocalcaneal ligament, posterior talofibular ligament), medial collateral ligament complex, spring ligament, Chopart joint ligaments (bifurcate ligament, dorsal talonavicular ligament, lateral calcaneocuboid ligament, long and short plantar ligaments), Lisfranc ligaments, sinus tarsi ligaments.